Snakes on a plane [videorecording (DVD)] - Ellis, David R. (David Richard), 1952-2013; Jackson, Samuel L.; Margulies, Julianna, 1966-; Phillips, Nathan (New Line Home Entertainment : Warner Home Video [distributor], 2007)
Nelville Flynn is escorting a witness on a plane that is bound for Los Angeles. The problem is that an assassin is bent on killing the witness. The assassin releases a crate containing about 450 deadly snakes onto the same plane. Nelville finds out and he becomes bent on doing his job and getting the snakes back where they belong - on land. If the snakes won't cooperate with Nelville, he will just have to send the snakes on to snake heaven.